Professional education, sustainability and citizenship in contemporary society - Barbosa, Soila (Revista Gestão da Produção Operações e Sistemas, 2012)
This article analyzes some aspects of professional education articulated with the sustainability and citizenship theme in Brazil. The new production and social organization of work model demands new qualifications to be and to remain employable. The study, a bibliographical revision, seeks selected subsidies of the Programme for International Student Assessment (PISA) to explain a slant in the interrelation among basic education, professional education and necessary requirements so proper citizens can support themselves, society and the economy. New paradigms are observed in the contemporary scenario, leading to transitions that demand different professional and social practices to reach sustainable development, which is carried out with the education of quality for all.Keywords: Professional Education; Education; Citizenship; Sustainability; Society.